DEVELOPMENT OF LEARNING MEDIA SMART BOOK TO IMPROVE UNDERSTANDING OF ELEMENTARY SCHOOL STUDENTS IN SCIENCE LEARNING - Hardiansyah, Framz; Zainuddin, Zainuddin; Sukitman, Tri; Astutik, Choli (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
This research is motivated by the problems in elementary schools, namely learning media that are not yet varied and the limitations of tools and materials in the learning process. The of this research development to (a) determine the attractiveness of this smart book media in the learning process on animal life cycle material and (b) determine the level of students' understanding after using the smart book media. This research method the Research and Development (R&D) type of ADDIE development model, which has five stages: analyze, design, development, implementation, and evaluation. The research design was a one-group pre-test and post-test design, with before-after experiments. The research was carried out at SDN Baban 1 Sumenep, with 30 fourth-grade students as tested subjects. The instruments used to obtain data were observation, questionnaires and achievement tests of learning outcomes. The results of the development carried out (a) The results of the trial to determine the level of attractiveness of smart book media in fourth-grade students obtained a percentage of 96.8%. (b) The level of students' understanding increasing, as seen from the average pre-test score of 60.3% and the post-test average value of 84.2%; it can be inferred that students effectively used the smart book media. The results of the t-test with a significance level of 0.05 obtained t-count = 5,542 > t-table = 1,699, which means t-count > t-table. These results prove that there were differences in students' understanding before and after using the smart book media for animal life cycle material (metamorphosis). Abstrak: Penelitian ini dilatarbelakangi pada masalah yang ditemukan di sekolah dasar yaitu media pembelajaran yang belum bervariatif, serta keterbatasan alat dan bahan dalam proses pembelajaran. Penelitian pengembangan ini bertujuan untuk (a) mengetahui daya tarik media smart book ini dalam proses pembelajaran materi daur hidup hewan dan (b) mengetahui tingkat pemahaman siswa setelah menggunakan media smart book. Metode penelitian ini menggunakan model pengembangan ADDIE tipe Research and Development (R&D), yang memiliki lima tahapan yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Desain penelitian ini adalah one group pre-test post-test design, dengan sebelum-sesudah eksperimen. Penelitian dilaksanakan di SDN Baban 1 Sumenep dengan subjek uji coba 30 siswa kelas IV. Instrumen yang digunakan untuk memperoleh data menggunakan observasi, angket dan tes ketercapaian hasil belajar. Hasil pengembangan yang dilakukan adalah (a) Hasil uji coba untuk mengetahui tingkat daya tarik media smart book pada siswa kelas IV diperoleh persentase sebesar 96,8%. (b) Tingkat pemahaman siswa meningkat, terlihat dari nilai rata-rata pre-test 60,3% dan nilai rata-rata post-test 84,2%; dapat dikatakan bahwa siswa efektif menggunakan media smart book. Hasil uji-t dengan taraf signifikansi 0,05 diperoleh t-hitung = 5,542 > t-tabel = 1,699 yang berarti t-hitung > t-tabel. Hasil tersebut membuktikan bahwa terdapat perbedaan pemahaman siswa sebelum dan sesudah menggunakan media smart book pada materi daur hidup hewan (metamorfosis).